CINTA KASIH AGAMA-AGAMA: HIDUP BERSAMA TUHAN DAMAI BERSAMA MANUSIA - MEDIA ZAINUL BAHRI (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Love is the sacred mission of world religions and it must be a real practice in daily life. The religion-based conflicts occurred recently shows that love in religions is disappeared. In this circumstance, love as sacred mission must urgently be reborn to eliminate the conflicts. This article elaborates love from some religions such as Islam, Christian, Hindu and Buddha. It also explains why the Semitics religions always matters and raises conflicts.